Fundraising Management of Darul Aitam Al Khoiriyah Lamongan Social Welfare Institute - Muklis Sanjaya; Istikomah Istikomah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The main problem raised in the research is how fundraising management in a social institution, conducted by the Social Welfare Institute Darul Aitam Al Khoiriyah. Based on these problems, the main purpose of this research is to find out how the forms of fundraising, supporting factors, and inhibitions of fundraising management and how the management of fundraising management for economic empowerment of the community. The results showed that: First, the fundraising management program is formulated based on community empowerment programs, one of which is the productive economic business self-entrepreneurship program (UEP), so that in the future the beneficiaries of fundraising no longer rely on donations or willingness but are economically self-sufficient. Second, the supporting factor in fundraising management is none other than the strength in maintaining the communication of institutions with the donator with various techniques and media used both electronic media and social media, while the obstacle factor of fundraising management is the HR factor that always has to be upgraded its ability so as not to miss the development of the times, as well as the existence of people who damage the image of social institutions so that the donators are more careful in distributing zakat, infaq, and Charity. Third, Lks Darul Aitam Al Khoiriyah fundraising strategy by applying systematic and measurable stages by the conditions in the field, namely the Introduction of Institutions to prospective new donors, Follow Up after the introduction, Accountability and supervision reports, Establish good communication with donors, Provide various forms of donation methods.